High-strength high-purity graphite phenolic aldehyde composite material for water lubricated bearing and preparation method thereof
Through the molding process and the optimization of formula, the compression strength and purity of the graphite phenolic composite material for water-lubricated bearings is improved, and the problems of low material performance and long process cycle in traditional processes are solved, achieving an efficient and simple forming process.
Patent Information
- Application Number
- CN202411325412.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-13
AI Technical Summary
The existing graphite phenolic composite materials for water-lubricated bearings have insufficient compression strength, complex molding process and long cycles, making it difficult to meet the high purity and high performance requirements of nuclear power pumps and valves.
Use the molding process to replace the traditional thermal isostatic pressing process, and use linear phenolic resin and high-carbon phenolic resin copolymer as the framework structure, combine with silicon nitride and other reinforced fillers to optimize the formulation and process flow, improve the compressive strength and purity of the material, and simplify molding. Craft.
The graphite phenolic composite material with high compression strength (250~310MPa) and high purity is achieved, shortening the molding process cycle from 30 days to 7 days, improving the mechanical and frictional properties of the material.
Smart Images

Figure CN119119677A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphite phenolic composite materials for water-lubricated bearings, and in particular relates to a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings and a preparation method thereof. Background Art
[0002] Water-lubricated bearings are one of the key components of nuclear power pumps and valves. Due to their special operating conditions, the materials need to have long service life, high purity (the content of low-melting-point metals, sulfur, and halogen elements is at the ppm level), extremely high compressive strength (≥250MPa) and excellent friction resistance. At present, there is no precedent for the development of such materials in China. The difficulty lies in the fact that the compressive strength of high-purity graphite phenolic composite materials prepared by traditional processes is between 150 and 230MPa. The compressive strength can be increased to more than 300MPa by infiltrating metal, but it will cause the metal content to exceed the standard. Therefore, the matching problem between the component structure and key performance of graphite phenolic composite materials is one of the key issues in the development of such materials. In addition, the existing isostatic pressing process is complex, the cycle is long, the roasting process is prone to cracking, and the densification efficiency is low. These problems plague the rapid iterative development of such materials, and a new type of graphite bearing material molding process is urgently needed.
[0003] The root of the problem is that the low skeleton strength and the complicated densification process of graphite phenolic composite material are the main reasons for the low compression strength and long process cycle of such materials. Phenolic resin is a low molecular weight mixture of phenol-formaldehyde addition and condensation reaction, and its curing reaction mainly includes the dehydration condensation reaction between methylol and the condensation reaction between methylol and the active hydrogen of phenol ring. The compression performance difference of phenolic resin with different chemical characteristic structures is very large, and the compression strength of composite material is positively correlated with the compression strength of resin. In addition, the composition of graphite phenolic composite material directly determines the purity, friction performance, molding process performance, etc. of composite material, so the formula of graphite phenolic composite material and component, molding process are key technologies of the present invention. The current technical difficulty is to meet the high purity requirements of material while realizing the high compression strength of graphite phenolic composite material, and the material preparation process is simple and efficient at the same time. Based on the above, it is urgent to develop a novel high-purity, low-cost, short-cycle, high-performance graphite phenolic composite material. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the inventors have conducted intensive research and provided a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings and a preparation method thereof. The graphite phenolic composite material has the characteristics of high purity, high compression strength and bending strength, excellent friction performance, etc., and can be used in the fields of wet-winding motor main pumps in the nuclear power field. The molding process is used instead of the traditional hot isostatic pressing process, thereby realizing the efficient preparation of graphite materials, and solving the technical problems of low key performance and long molding process cycle of traditional graphite phenolic composite materials.
[0005] The technical solution provided by the present invention is as follows:
[0006] In a first aspect, a high-strength and high-purity graphite phenolic composite material for a water-lubricated bearing is made of the following raw materials in parts by weight:
[0007]
[0008] In a second aspect, a method for preparing a high-strength and high-purity graphite phenolic composite material for a water-lubricated bearing comprises: mixing graphite powder, linear phenolic resin, high-carbon phenolic resin, reinforcing filler, curing agent and dispersion medium to obtain a slurry, paving and drying the slurry to form a prepreg, and subjecting the prepreg to a molding curing and heating post-treatment process to form a graphite phenolic composite material;
[0009] Specifically, the preparation method comprises the following steps: dissolving linear phenolic resin in a dispersion medium, stirring until completely dissolved, adding a curing agent, and stirring; after completely dissolved, adding a high carbon phenolic resin, stirring, and the resin solution is ready for use;
[0010] Dissolve graphite powder in the above resin solution, stir evenly, add reinforcing filler, continue stirring to obtain slurry;
[0011] The slurry is evenly spread and dried at 20-40° C. to obtain a prepreg block, and the block is crushed and sieved to obtain a graphite phenolic composite material prepreg;
[0012] Putting the graphite phenolic composite material prepreg into a mold, pressing and curing, and cooling;
[0013] The molded and solidified material is subjected to high temperature treatment at 170-280° C. to obtain a high-strength and high-purity graphite phenolic composite material for a water-lubricated bearing.
[0014] A high-strength and high-purity graphite phenolic composite material for water-lubricated bearings and a preparation method thereof provided by the present invention have the following beneficial effects:
[0015] (1) The present invention provides a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings and a preparation method thereof, which uses linear phenolic resin and high-carbon phenolic resin copolymer as a skeleton structure and reinforcing fillers such as silicon nitride as rigid components to increase the crack propagation path and thus improve the compression strength of graphite phenolic. By optimizing the formula of the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings, the problem of low key performance of traditional bearing graphite materials is effectively solved. The high-purity graphite phenolic composite material has a compression strength of 250 to 310 MPa and a bending strength of 80 to 110 MPa. The wear loss after continuous friction in a 90°C water environment for 10 hours does not exceed 0.035 mm, and has excellent mechanical properties and friction properties.
[0016] (2) The present invention provides a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings and a preparation method thereof, which adopts a molding process instead of a traditional hot isostatic pressing process, and reduces the graphite material molding process cycle from the original 30 days to 7 days. By rationally designing the graphite phenolic composite material molding process, the technical problems of low key performance of traditional bearing graphite materials and long molding process cycle are cleverly solved;
[0017] (3) The present invention provides a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings and a preparation method thereof, and obtains a high-purity composite material by controlling the content of impurities such as metal elements and halogen elements in graphite powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a picture of a real sample of the engineering size of the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings in Example 1 of the present invention;
[0019] Figure 2 This is a microscopic morphology picture of a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings according to Example 1 of the present invention;
[0020] Figure 3 This is a CT inspection picture of a random sample of high-strength and high-purity graphite phenolic composite material for water-lubricated bearings according to Example 1 of the present invention. DETAILED DESCRIPTION
[0021] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0022] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0023] The present invention provides a high-strength and high-purity graphite phenolic composite material for a water-lubricated bearing, which is made of the following raw materials in parts by weight:
[0024]
[0025] Preferably, the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings is made of the following raw materials in parts by weight:
[0026]
[0027] Further preferably, the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings is made of the following raw materials in parts by weight:
[0028]
[0029]
[0030] More preferably, the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings is made of the following raw materials in parts by weight:
[0031]
[0032] In a preferred embodiment, the graphite powder contains ≤50 ppm of metal elements and ≤50 ppm of halogen elements, and has an average particle size of 10 to 100 μm.
[0033] In a preferred embodiment, the linear phenolic resin is a thermoplastic phenolic resin, with a free phenol content of ≤9 and a weight average molecular weight of 6000 to 10000 g / mol.
[0034] In a preferred embodiment, the high carbon phenolic resin is a thermosetting phenolic resin with a solid content of ≥65% (GJB1059.1), a 50% solution rotational viscosity of ≤70 mPa·s (GJB1059.2), a free phenol content of ≤12% (GJB1059.3), a gel time of 150 to 210 s (GJB1059.4), and a residual carbon rate of ≥65% at 800°C. For example, the high carbon phenolic resin produced by East China University of Science and Technology is used, and the chemical structure is
[0035]
[0036] In a preferred embodiment, the reinforcing filler is at least one of silicon nitride powder, silicon carbide powder or silicon dioxide powder, preferably silicon nitride powder. The average particle size of the reinforcing filler is 1 to 200 μm, preferably 10 to 60 μm.
[0037] In a preferred embodiment, the curing agent is a curing agent for linear phenolic resin, preferably hexamethylenetetramine.
[0038] The high-purity graphite phenolic composite material has a compression strength of 250-310MPa, a bending strength of 80-110MPa, and a wear loss of no more than 0.035mm after continuous friction in a 90°C water environment for 10 hours. The metal elements are ≤50ppm, and the halogen elements are ≤50ppm.
[0039] The present invention also provides a method for preparing a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings, comprising: stirring and mixing graphite powder, linear phenolic resin, high-carbon phenolic resin, reinforcing filler, curing agent and dispersion medium to obtain a slurry, the slurry is spread and dried to form a prepreg, and the prepreg is subjected to high-temperature molding and post-processing to form a graphite phenolic composite material.
[0040] The preparation method of the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings specifically comprises:
[0041] (1) Dissolve the linear phenolic resin in a dispersion medium at 25-45° C. according to the mass ratio, stir for 1-2 hours until it is completely dissolved, add the curing agent, and stir for 3-4 hours; after it is completely dissolved, add the high carbon phenolic resin, stir for 1-2 hours, and the resin solution is ready for use;
[0042] In this step, the dispersion medium is an alcohol or ester solvent, such as methanol, anhydrous ethanol, ethyl acetate, etc. Based on safety considerations, anhydrous ethanol is preferred.
[0043] The dispersion medium is 50 to 150 parts by mass, preferably 60 to 140 parts by mass, more preferably 80 to 120 parts by mass, and most preferably 90 to 110 parts by mass based on 100 parts by mass of the graphite powder.
[0044] (2) dissolving graphite powder in the above resin solution according to the mass fraction ratio, adding reinforcing filler after stirring for 3 to 4 hours, and continuing to stir for 1 to 2 hours to obtain slurry for standby use;
[0045] (3) The slurry is evenly spread on the release paper with a thickness not exceeding 3 mm, and dried at 20 to 40° C. for 48 to 72 hours to obtain a prepreg block. The block is placed in a powdering machine for powdering and then passed through a 10 to 20 mesh sieve to obtain a graphite phenolic composite material prepreg;
[0046] (4) placing the graphite phenolic composite material prepreg obtained in step (3) into a mold, heating the prepreg to 85-95° C. at a heating rate of 0.5-1.5° C. / min, starting to pressurize the prepreg so that it bears a pressure of 120-150 MPa, reacting at a constant temperature for 1-5 h, heating the prepreg to 120-130° C. at a heating rate of 0.5-1.5° C. / min, reacting at a constant temperature for 1-3 h, heating the prepreg to 160-200° C. at a heating rate of 0.5-1.5° C. / min, reacting at a constant temperature for 3-6 h, cooling the prepreg naturally, and setting it aside for use.
[0047] (5) The material obtained in step (3) is placed in a forced air drying oven at 170-280° C. for 4-6 hours to obtain a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings.
[0048] In the method for preparing the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings, the stirring rate is 100-200 rpm in all the remaining steps except those already specified.
[0049] Example
[0050] In the embodiments and comparative examples, except as otherwise specified, the average particle size of the graphite powder is 24 μm, and the metal and halogen elements are ≤50 ppm; the free phenol content of the linear phenolic resin is 5.4%, and the weight average molecular weight is 8240; the high carbon phenolic resin adopts the high carbon phenolic resin produced by East China University of Science and Technology; and the average particle size of silicon nitride is 55 μm.
[0051] Example 1
[0052] A high-strength and high-purity graphite phenolic composite material for water-lubricated bearings, the preparation method of which comprises the following steps:
[0053] Preparation of prepreg: dissolve 15.5 parts of linear phenolic resin in 110 parts of ethanol at 35°C, stir for 1.5 hours until completely dissolved, add 2.5 parts of hexamethylenetetramine, and stir for 3.5 hours; after complete dissolution, add 5.5 parts of high-carbon phenolic resin and stir for 1.5 hours; dissolve 100 parts of graphite powder in the above resin solution, stir for 3.5 hours, then add 6.5 parts of silicon nitride, continue stirring for 1 hour to obtain slurry; spread the above slurry evenly on release paper with a thickness not exceeding 3 mm, dry at 30°C for 60 hours to obtain prepreg blocks, place the blocks in a powdering machine for powdering, and then pass through a 20-mesh sieve to obtain graphite phenolic composite material prepreg.
[0054] Graphite phenolic aldehyde curing: put the prepreg into the mold, heat it to 90℃ at a heating rate of 1℃ / min, start pressurizing the prepreg to bear 135MPa, react at constant temperature for 3h, heat it to 125℃ at a heating rate of 1℃ / min, react at constant temperature for 2h, heat it to 180℃ at a heating rate of 1℃ / min, react at constant temperature for 4.5h, and cool naturally. The cured graphite phenolic aldehyde composite material is placed in a blast drying oven, and after post-treatment at 200℃ for 4h, a high-strength and high-purity graphite phenolic aldehyde composite material for water-lubricated bearings is obtained.
[0055] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Example 1 has a density of 1.85 g / cm 3 The average compression strength is 302MPa, the bending strength is 110MPa, the wear volume is 0.018mm after continuous friction in 90℃ water environment for 10h, and the average friction coefficient is 0.26.
[0056] Figure 1 This is a picture of a real sample of the engineering size of the high-strength and high-purity graphite phenolic composite material for water-lubricated bearings in Example 1 of the present invention; Figure 2 This is a microscopic morphology picture of a high-strength and high-purity graphite phenolic composite material for water-lubricated bearings according to Example 1 of the present invention; Figure 3 This is a CT inspection picture of a random sample of high-strength and high-purity graphite phenolic composite material for water-lubricated bearings according to Example 1 of the present invention.
[0057] Example 2
[0058] A high-strength and high-purity graphite phenolic composite material for water-lubricated bearings, the preparation method of which comprises the following steps:
[0059] Preparation of prepreg: dissolve 2 parts of linear phenolic resin in 50 parts of ethanol at 25-45°C, stir for 1 hour until completely dissolved, add 0.1 parts of hexamethylenetetramine, and stir for 3 hours; after complete dissolution, add 20 parts of high-carbon phenolic resin and stir for 1 hour; dissolve 100 parts of graphite powder in the above resin solution, stir for 3 hours, add 0.1 parts of silicon nitride, continue stirring for 1 hour to obtain slurry; spread the above slurry evenly on release paper with a thickness not exceeding 3 mm, dry at 20°C for 48 hours to obtain prepreg blocks, place the blocks in a powdering machine for powdering, and then pass through a 20-mesh sieve to obtain graphite phenolic composite material prepreg.
[0060] Graphite phenolic aldehyde curing: put the prepreg into the mold, heat it to 85℃ at a heating rate of 0.5℃ / min, start pressurizing the prepreg to bear 120MPa, react at constant temperature for 1h, heat it to 120℃ at a heating rate of 0.5℃ / min, react at constant temperature for 1h, heat it to 160℃ at a heating rate of 0.5℃ / min, react at constant temperature for 3h, and cool naturally. The cured graphite phenolic aldehyde composite material is placed in a blast drying oven, and after post-treatment at 170℃ for 4h, a high-strength and high-purity graphite phenolic aldehyde composite material for water-lubricated bearings is obtained.
[0061] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Example 2 has a density of 1.81 g / cm 3 The average compression strength is 252MPa, the bending strength is 82MPa, the wear volume is 0.031mm after continuous friction in 90℃ water environment for 10h, and the average friction coefficient is 0.22.
[0062] Example 3
[0063] A high-strength and high-purity graphite phenolic composite material for water-lubricated bearings, the preparation method of which comprises the following steps:
[0064] Preparation of prepreg: dissolve 20 parts of linear phenolic resin in 150 parts of ethanol at 35°C, stir for 1 to 2 hours until completely dissolved, add 5 parts of hexamethylenetetramine, and stir for 4 hours; after complete dissolution, add 2 parts of high-carbon phenolic resin and stir for 2 hours; dissolve 100 parts of graphite powder in the above resin solution, stir for 4 hours, then add 1 part of silicon nitride, continue stirring for 1 hour to obtain slurry; spread the above slurry evenly on release paper with a thickness not exceeding 3 mm, dry at 40°C for 72 hours to obtain prepreg blocks, place the blocks in a powdering machine for powdering, and then pass through a 20-mesh sieve to obtain graphite phenolic composite material prepreg.
[0065] Graphite phenolic aldehyde curing: put the prepreg into the mold, heat it to 95℃ at a heating rate of 1.5℃ / min, start pressurizing the prepreg to bear 150MPa, react at constant temperature for 5h, heat it to 130℃ at a heating rate of 1.5℃ / min, react at constant temperature for 3h, heat it to 200℃ at a heating rate of 1.5℃ / min, react at constant temperature for 6h, and cool naturally. The cured graphite phenolic aldehyde composite material is placed in a blast drying oven, and after post-treatment at 280℃ for 4h, a high-strength and high-purity graphite phenolic aldehyde composite material for water-lubricated bearings is obtained.
[0066] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Example 3 has a density of 1.81 g / cm 3 The average compression strength is 266MPa, the bending strength is 93MPa, the wear volume is 0.029mm after continuous friction in 90℃ water environment for 10h, and the average friction coefficient is 0.19.
[0067] Example 4
[0068] A high-strength and high-purity graphite phenolic composite material for water-lubricated bearings, the preparation method of which comprises the following steps:
[0069] Preparation of prepreg: dissolve 17 parts of linear phenolic resin in 120 parts of ethanol at 35°C, stir for 1.5 hours until completely dissolved, add 4 parts of hexamethylenetetramine, and stir for 3.5 hours; after complete dissolution, add 4 parts of high-carbon phenolic resin and stir for 1.5 hours, dissolve 100 parts of graphite powder in the above resin solution, stir for 4 hours, add 5 parts of silicon nitride, continue stirring for 1 hour, and obtain slurry; spread the above slurry evenly on release paper with a thickness not exceeding 3mm, dry at 30°C for 60 hours to obtain prepreg blocks, place the blocks in a powdering machine for powdering, and then pass through a 20-mesh sieve to obtain graphite phenolic composite material prepreg.
[0070] Graphite phenolic aldehyde curing: put the prepreg into the mold, heat it to 90℃ at a heating rate of 1℃ / min, start pressurizing the prepreg to bear 135MPa, react at constant temperature for 3h, heat it to 125℃ at a heating rate of 1℃ / min, react at constant temperature for 2h, heat it to 180℃ at a heating rate of 1℃ / min, react at constant temperature for 4.5h, and cool naturally. The cured graphite phenolic aldehyde composite material is placed in a blast drying oven, and after post-treatment at 200℃ for 4h, a high-strength and high-purity graphite phenolic aldehyde composite material for water-lubricated bearings is obtained.
[0071] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Example 4 has a density of 1.85 g / cm 3The average compression strength is 282MPa, the bending strength is 99MPa, the wear volume is 0.022mm after continuous friction in 90℃ water environment for 10h, and the average friction coefficient is 0.25.
[0072] Comparative Example
[0073] Comparative Example 1
[0074] The comparative example 1 is consistent with the example 1, except that the linear phenolic resin and the hexamethylenetetramine curing agent are not used in the raw materials of the graphite phenolic composite material, and the amount of the high carbon phenolic resin is increased to 21 parts.
[0075] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Comparative Example 1 has a density of 1.81 g / cm 3 The average compressive strength is 192MPa.
[0076] Comparative Example 2
[0077] Comparative Example 2 is consistent with Example 1, except that high carbon phenolic resin is not used in the raw materials of the graphite phenolic composite material, and the amount of linear phenolic resin is increased to 21 parts.
[0078] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Comparative Example 2 has a density of 1.82 g / cm 3 The average compressive strength is 212MPa.
[0079] Comparative Example 3
[0080] The comparative example 3 is consistent with the example 1, except that the amount of the linear phenolic resin in the raw material of the graphite phenolic composite material is increased to 25 parts, and the amount of the high carbon phenolic resin remains unchanged.
[0081] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in this comparative example 3 has a density of 1.73 g / cm 3 The average compressive strength is 265MPa.
[0082] Comparative Example 4
[0083] The comparative example 4 is consistent with the example 1, except that the amount of the high carbon phenolic resin in the raw material of the graphite phenolic composite material is increased to 25 parts, and the amount of the linear phenolic resin remains unchanged.
[0084] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Comparative Example 4 has a density of 1.65 g / cm 3 The average compression strength is 252MPa.
[0085] Comparative Example 5
[0086] The comparative example 5 is consistent with the example 1, except that the weight average molecular weight of the linear phenolic resin in the raw material of the graphite phenolic composite material is 1235 g / mol.
[0087] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in this comparative example 5 has a density of 1.84 g / cm 3 The average compressive strength is 186MPa.
[0088] Comparative Example 6
[0089] This comparative example 6 is consistent with Example 1, except that the solid content of the thermosetting phenolic resin in the raw materials of the graphite phenolic composite material is 57% (GJB1059.1), the 50% solution rotational viscosity is 15 mPa·s (GJB1059.2), the free phenol content is 16% (GJB1059.3), the gel time is 122 s (GJB1059.4), and the residual carbon rate at 800°C is 61%.
[0090] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in this comparative example 6 has a density of 1.85 g / cm 3 The average compression strength is 166MPa.
[0091] Comparative Example 7
[0092] Comparative Example 7 is consistent with Example 1, except that the raw material of the graphite phenolic composite material does not contain silicon nitride powder.
[0093] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in this comparative example 7 has a density of 1.81 g / cm 3 The average compressive strength is 245MPa.
[0094] Comparative Example 8
[0095] The comparative example 8 is consistent with the example 1, and the only difference is that the reinforcing filler in the raw material of the graphite phenolic composite material is clay.
[0096] The high-strength and high-purity graphite phenolic composite material for water-lubricated bearings obtained in Comparative Example 8 has a density of 1.83 g / cm 3 The average compressive strength is 225MPa.
[0097] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0098] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.
Claims
1. A graphite phenolic composite material for water-lubricated bearings, characterized in that: Made from the following raw materials in parts by weight:
2. The graphite phenolic composite material for water-lubricated bearings according to claim 1, characterized in that: The graphite powder contains metal elements ≤50ppm and halogen elements ≤50ppm, and the average particle size is 10-100μm.
3. The graphite phenolic composite material for water-lubricated bearings according to claim 1, characterized in that: The linear phenolic resin is a thermoplastic phenolic resin with a weight average molecular weight of 6000 to 10000 g / mol.
4. The graphite phenolic composite material for water-lubricated bearings according to claim 1, characterized in that: The high carbon phenolic resin is a thermosetting phenolic resin with a solid content of ≥65%, a 50% solution rotational viscosity of ≤70 mPa·s, a free phenol content of ≤12%, a gel time of 150-210s, and a residual carbon rate of ≥65% at 800°C.
5. The graphite phenolic composite material for water-lubricated bearings according to claim 1, characterized in that: The reinforcing filler is at least one of silicon nitride powder, silicon carbide powder or silicon dioxide powder.
6. The graphite phenolic composite material for water-lubricated bearings according to claim 1, characterized in that: The average particle size of the reinforcing filler is 1 to 200 μm.
7. The graphite phenolic composite material for water-lubricated bearings according to claim 1, characterized in that: The curing agent is hexamethylenetetramine.
8. A method for preparing the graphite phenolic composite material for water-lubricated bearings according to any one of claims 1 to 7, characterized in that: Graphite powder, linear phenolic resin, high carbon phenolic resin, reinforcing filler, curing agent and dispersion medium are stirred and mixed to obtain slurry, the slurry is formed into prepreg after coating and drying, and the prepreg is formed into graphite phenolic composite material after molding curing and heating post-treatment process.
9. The method for preparing the graphite phenolic composite material for water-lubricated bearings according to claim 8, characterized in that: Specifically include: Dissolve the linear phenolic resin in the dispersion medium, stir until completely dissolved, add the curing agent, and stir; After it is completely dissolved, add high carbon phenolic resin, stir, and the resin solution is ready for use; Dissolve graphite powder in the above resin solution, stir evenly, add reinforcing filler, continue stirring to obtain slurry; The slurry is evenly spread and dried at 20-40° C. to obtain a prepreg block, and the block is crushed and sieved to obtain a graphite phenolic composite material prepreg; Putting the graphite phenolic composite material prepreg into a mold, pressing and curing, and cooling; The molded and solidified material is subjected to high temperature treatment at 170-280° C. to obtain a high-strength and high-purity graphite phenolic composite material for a water-lubricated bearing.
10. The method for preparing the graphite phenolic composite material for water-lubricated bearings according to claim 9, characterized in that: The steps of placing the graphite phenolic composite material prepreg into a mold, molding and curing, and cooling specifically include: placing the graphite phenolic composite material prepreg into a mold, heating the temperature to 85-95°C at a heating rate of 0.5-1.5°C / min, starting to pressurize the prepreg so that it can withstand a pressure of 120-150MPa, reacting at a constant temperature for 1-5h, heating the temperature to 120-130°C at a heating rate of 0.5-1.5°C / min, reacting at a constant temperature for 1-3h, heating the temperature to 160-200°C at a heating rate of 0.5-1.5°C / min, reacting at a constant temperature for 3-6h, and cooling naturally.
